Beyond Emotional Intelligence: A Multidimensional Model of Self-Awareness and its Role in Predicting Leadership Effectiveness - Shahzadi, Shazia; Azad, Naureen; Mahar, Sourath; Mahar, Abdul Qayoom (2025)
This study re-conceptualizes self-awareness in leadership by integrating emotional, cognitive, and social intelligence into a triadic model. Addressing the methodological shortcomings of traditional difference score approaches, the study employs a novel correlational method to measure self-awareness over time. Data were collected from 72 manager-subordinate dyads across various organizational sectors in Pakistan. Managers completed two self-assessments two weeks apart, while subordinates rated their leadership behaviors using the Leader Behavior Description Questionnaire (LBDQ). Regression analyses revealed that social intelligence was the only significant predictor of subordinate-rated leadership effectiveness. Emotional and cognitive intelligence, as well as self-awareness measured through both correlational and difference score approaches, did not significantly predict leadership behavior. These findings underscore the cultural complexities of measuring self-awareness in high power-distance contexts and highlight the need for culturally attuned, multidimensional assessment tools. The study advocates for the integration of social intelligence in leadership development frameworks and offers insights for future research on leadership assessment and training.